The numerical modelling of electromagnetic fields in biological structures under RF radiation - Ying, Jian Ling. (2009)
The research area on electromagnetic scattering and absorption is a classical one and is crucial to the study of various problems of practical significance. One important application is the study to quantify the potential electromagnetic radiation effects to biological structures such eis human tissues. For ethical reasons, the task is now possible by the use highly sophisticated and realistic numerical models.